2008
DOI: 10.1254/jphs.08059fp
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Somnolence in the Daytime Caused by Drugs Used for Neuropathic Pain

Abstract: Abstract. In the present study, the characteristics of the sleep features of amitriptyline, mexiletine, and N-(4-tertiarybutylphenyl)-4-(3-cholorphyridin-2-yl)tetrahydropyradine-1(2H)-carbox-amide (BCTC) were studied. Electrodes were chronically implanted into the frontal cortex and the dorsal neck muscles of rats for electroencephalogram (EEG) and electromyogram (EMG) measurements, respectively. EEG and EMG were recorded with an electroencephalograph, and SleepSign ver. 2.0. was used for sleep-wake state anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Therefore, it is reasonable to presume that aripiprazole inhibits dopaminergic function in MK-801-treated rats. In addition, Hirase et al (11) reported that a 5-HT 1A -receptor agonist, tandspiron, caused a decrease in sleep latency in sleep-disturbed rats; therefore, it is reasonable to consider that the antagonistic activity of aripiprazole on the increase in sleep latency induced by MK-801 was exhibited via the 5-HT 1A receptor. As shown previously, risperidone caused an antagonizing effect on the increase in hourly awake time induced by MK-801, although the duration was relatively short.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is reasonable to presume that aripiprazole inhibits dopaminergic function in MK-801-treated rats. In addition, Hirase et al (11) reported that a 5-HT 1A -receptor agonist, tandspiron, caused a decrease in sleep latency in sleep-disturbed rats; therefore, it is reasonable to consider that the antagonistic activity of aripiprazole on the increase in sleep latency induced by MK-801 was exhibited via the 5-HT 1A receptor. As shown previously, risperidone caused an antagonizing effect on the increase in hourly awake time induced by MK-801, although the duration was relatively short.…”
Section: Discussionmentioning
confidence: 99%
“…2.0, according to the previously described criteria (16,17). As a final step, the defined sleep-wake stages were examined visually and corrected if necessary.…”
Section: Sleep-wake State Analysismentioning
confidence: 99%
“…2.0. The power spectrum densities, integrated and averaged, could be divided into 4 frequency areas: delta wave (0.5 -4 Hz), theta wave (4 -8 Hz), alpha wave (8 -13 Hz), and beta wave (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Delta activity (%) was calculated by the following equation: Delta activity (%) = delta wave power density in the drug administration period / delta wave power density in the vehicle administration period in each animal × 100.…”
Section: Calculation Of Delta Activity During Non-rem Sleepmentioning
confidence: 99%
“…Recordings were conducted as described previously. 12,13) The signals were amplified and filtered (EEG, 0.5-30 Hz; EMG, 16-60 Hz), then digitized at a sampling rate of 128 Hz, and recorded by SleepSign ver. 2.0 (Kissei Comtec, Nagano, Japan) data acquisition program.…”
Section: Methodsmentioning
confidence: 99%